039 Peripheral administration of vasopressors in transport. Issue 12 (21st November 2019) - Gervin, Kevin; Corfield, Alasdair; Queen, Anton
Abstract : Background: Management of shocked patients frequently requires vasopressor (epinephrine/norepinephrine) administration. Although less potent vasoactive agents are commonly delivered peripherally, historical concerns surround peripheral epinephrine and particularly norepinephrine use; these are primarily administered as infusions via central venous catheter (CVC). Concerns centre on potential extravasation and subsequent skin or tissue necrosis. However, recent studies suggest risks maybe lower than perceived. In the pre-hospital setting, circumstance may demand use of epinephrine/norepinephrine but preclude CVC insertion. In this study we assessed current practice for peripheral vasopressor usage in a national pre-hospital and retrieval service and associated complications. Method and results: A retrospective, cohort study, using routinely collected data from the EMRS electronic record, cross-referenced against contemporaneous paper medical records from 2004–2018. All primary (pre-hospital) and secondary (from remote/rural healthcare facilities) patients over the age of 16 requiring peripheral vasopressors for shock were included. Data was collected on demographic information, retrieval site and mode of transport, vasopressor used, shock type, duration of use and subsequent complications. Complications were defined as immediate, noted by retrieval team on mission paperwork; or delayed, noted at 24-hour follow-up. Descriptive statistics for cohort study have been used and all analyses conducted using Stata v12.0 Conclusions: 6093 missions were reviewed. Vasopressors were administered to 6.8% (417/6093) of patients. Epinephrine infusions were administered to 129 patients and 307 required norepinephrine (19 received both). Peripheral vasopressor infusions were used in 16.1% (67/417) of infusions. Of peripheral infusions, 40 patients received epinephrine and 30 received norepinephrine (three received both). Three epinephrine infusions were during primary missions, all norepinephrine infusions were on secondary retrievals. Distributive shock was the commonest indication for both (47.5% & 73.3%). There were no reported complications during missions or at 24-hours. Results suggest pre-hospital use of peripheral epinephrine/norepinephrine is relatively common and safe, with no complications reported across 15 years of practice.